Winter wheat (Triticum aestivum) response to Barley yellow dwarf virus at various nitrogen application rates in the presence and absence of its aphid vector, Rhopalosiphum padi. Issue 2 (25th January 2019) - Liang, Xi; Rashidi, Mahnaz; Rogers, Christopher W.; Marshall, Juliet M.; Price, William J.; Rashed, Arash
Abstract: Barley yellow dwarf (BYD) is one of the most common diseases of cereal crops, caused by the phloem‐limited, cereal aphid‐borne Barley yellow dwarf virus (BYDV) (Luteoviridae). Delayed planting and controlling aphid vector numbers with insecticides have been the primary approaches to manage BYD. There is limited research on nitrogen (N) application effects on plant growth, N status, and water use in the BYDV pathosystem in the absence of aphid control. Such information will be essential in developing a post‐infection management plan for BYDV‐infected cereals. Through a greenhouse study, we assessed whether manipulation of N supply to BYDV‐infected winter wheat, Triticum aestivum L. (Poaceae), in the presence or absence of the aphid vector Rhopalosiphum padi L. (Hemiptera: Aphididae), could improve N and/or water uptake, and subsequently promote plant growth. Similar responses of shoot biomass and of water and N use efficiencies to various N application rates were observed in both BYDV‐infected and non‐infected plants, suggesting that winter wheat plants with only BYDV infection may be capable of outgrowing infection by the virus. Plants, which simultaneously hosted aphids and BYDV, suffered more severe symptoms and possessed higher virus loads than those infected with BYDV only. Moreover, in plants hosting both BYDV and aphids, aphid pressure was positively associated with N concentration within plant tissue, suggesting that N application and N concentration within foliar tissue may alter BYDV replication indirectly through their influence on aphid reproduction. Even though shoot biomass, tissue N concentration, and water use efficiency increased in response to increased N application, decision‐making on N fertilization to plants hosting both BYDV and aphids should take into consideration the potential of aphid outbreak and/or the possibility of reduced plant resilience to environmental stresses due to decreased root growth. Abstract : This work evaluates the effects of nitrogen supply on Barley yellow dwarf virus (BYDV) titer and disease progress in winter wheat. Nitrogen supply did not affect BYDV titer but could promote multiplication of the vector aphid Rhopalosiphum padi (Hemiptera: Aphididae). As nitrogen may also reduce early‐stage root development, it is suggested that ideally nitrogen application in high‐risk BYDV areas is conducted when aphids are absent, or following aphid control. However, this needs to be confirmed in field experiments.